TNF-α–Induced miR-21-3p Promotes Intestinal Barrier Dysfunction by Inhibiting MTDH Expression - Jiang, Zhifeng; Yang, Feiyu; Qie, Jingbo; Jin, Chaoyuan; Zhang, Feng; Shen, Jie; Zhang, Lin (Frontiers in Pharmacology, 2021)
Intestinal barrier dysfunction is characterized by increased intestinal permeability to lumen endotoxin, showing remarkable predisposition to immune enteropathy, and colorectal cancer tumor necrosis factor (TNF)-α is associated with this pathological process, while the mechanism remains unknown. In this study, different doses of TNF-α were used for Caco-2 cell treatment. We discovered that miR-21-3p expression was obviously increased by TNF-α in a dose-dependent manner. Further study demonstrated that TNF-α could upregulate miR-21-3p expression through the NF-κB signaling pathway. Then, TargetScan and miRWalk miRNA–mRNA interaction prediction online tools were introduced, and metadherin (MTDH) was screened out as a potential target of miR-21-3p. We subsequently found that miR-21-3p could directly target the 3′-untranslated region (UTR) of MTDH mRNA and inhibit its expression. Furthermore, it was demonstrated that miR-21-3p could regulate the Wnt signaling pathway by targeting MTDH mRNA, suggesting the effect of miR-21-3p/MTDH/Wnt axis on intestinal barrier dysfunction. Our findings provide a novel potential biomarker and therapeutic target for intestinal barrier dysfunction and related diseases.